Evaluation of the seismic performance of a code-conforming reinforced-concrete frame building from seismic hazard to collapse safety and economic losses. - Goulet, Christine A.
A state-of-the-art seismic performance assessment is illustrated through application to a reinforced-concrete moment-frame building designed per current (2003) building code provisions. Performance is quantified in terms of economic losses and collapse safety. The assessment includes site-specific seismic hazard analyses, nonlinear dynamic structural response simulations to collapse, damage analyses, and loss estimation. When selecting ground motion records for nonlinear dynamic analyses that are consistent with a target hazard level expressed in terms of a response spectral value at the building's fundamental period, it is important to consider the response spectral shape, especially when considering higher hazard levels. This was done through the parameter commonly denoted by ε. Neglecting these effects during record selection is shown to lead to a factor of 5?10 overestimation of mean annual collapse rate. Structural response simulations, which properly account for uncertainties in ground motions and structural modelling, indicate a 2?7% probability of collapse for buildings subjected to motions scaled to a hazard level equivalent to a 2% probability of exceedance in 50 years. The probabilities of component damage and the means and coefficients of variation of the repair costs are calculated using fragility functions and repair-cost probability distributions. The calculated expected annual losses for various building design variants range from 0.6 to 1.1% of the replacement value, where the smaller losses are for above-code design variants and the larger losses are for buildings designed with minimum-code compliance. Sensitivity studies highlight the impact of key modelling assumptions on the accurate calculation of damage and the associated repair costs.
Keywords: Seismic; Performance; Assessment; Building; Epsilon; Collapse; Losses